# Derivatives of inverse trigonometric functions | Class 12 Maths

## Derivative of Inverse Sine Function

$f(x)= sin^{–1} x$
Let $y = sin^{–1} x$
siny =x
Differentiating both sides w.r.t. x, we get
$cos y \frac {dy}{dx}=1$
or
$\frac {dy}{dx} = \frac {1}{cos y} = \frac {1}{cos sin^{–1} x}$
Clearly we can see that x cannot be -1 or 1 as then it will then become undefined. Therefore $x \in (-1,1)$
Also
$cos^2 y=1 -sin^2 y$
$cos^2 y = 1 -x^2$
As $sin^{–1} x$ lies between $(-\pi/2, \pi/2)$, cos y is always positive
Hence
$cos y = \sqrt {1-x^2}$
Therefore
$\frac {dy}{dx} = \frac {1}{\sqrt {1-x^2}}$
Domain of f' is (-1,1)

## Derivative of Inverse cos Function

$f(x)= cos^{–1} x$
Let $y = cos^{–1} x$
cosy =x
Differentiating both sides w.r.t. x, we get
$-sin y \frac {dy}{dx}=1$
or
$\frac {dy}{dx} = -\frac {1}{sin y} = -\frac {1}{sin cos^{–1} x}$
Clearly we can see that x cannot be -1 or 1 as then it will then become undefined. Therefore $x \in (-1,1)$
Also
$sin^2 y=1 -cos^2 y$
$sin^2 y = 1 -x^2$
As $cos^{–1} x$ lies between $(0, \pi)$, sin y is always positive
Hence
$sin y = \sqrt {1-x^2}$
Therefore
$\frac {dy}{dx} = -\frac {1}{\sqrt {1-x^2}}$
Domain of f' is (-1,1)

## Derivative of Inverse tan Function

$f(x)= tan^{–1} x$
Let $y = tan^{–1} x$
tany =x
Differentiating both sides w.r.t. x, we get
$sec^2 y \frac {dy}{dx}=1$
or
$\frac {dy}{dx} = \frac {1}{sec^2 y} = \frac {1}{1 + tan^2 y}= \frac {1}{1 + x^2}$
Domain of f' is R

## Derivative of Inverse cot Function

$f(x)= cot^{–1} x$
Let $y = cot^{–1} x$
cot y =x
Differentiating both sides w.r.t. x, we get
$-cosec^2 y \frac {dy}{dx}=1$
or
$\frac {dy}{dx} = -\frac {1}{cosec^2 y} = \frac {1}{1 + cot^2 y}= -\frac {1}{1 + x^2}=$
Domain of f' is R

## Derivative of Inverse cosec Function

$f(x)= cosec^{–1} x$
Let $y = cosec^{–1} x$
cosec y =x
Differentiating both sides w.r.t. x, we get
$-cosec y cot y \frac {dy}{dx}=1$
or
$\frac {dy}{dx} =- \frac {1}{cosec y cot y}$
Clearly we can see that x cannot be -1 or 1 as then it will then become undefined. Therefore $x \in R -[-1,1]$
Also
$cot^2 y=cosec^2 y -1$
$cot^2 y =x^2 -1$
As $cosec^{–1} x$ lies between $(-\pi/2, \pi/2)$, cot y will be positive and negative respectively
Hence
When x is negative $cot y = \sqrt {x^2 -1}$
When x is psotive $cot y =- \sqrt {x^2 -1}$
Therefore
When x is negative $\frac {dy}{dx} = -\frac {1}{- x \sqrt {x^2 -1}}=-\frac {1}{ |x| \sqrt {x^2 -1}}$ When is positive $\frac {dy}{dx} = -\frac {1}{ x \sqrt {x^2 -1}}=-\frac {1}{ |x| \sqrt {x^2 -1}}$ Domain of f' is R -[-1,1]

## Derivative of Inverse sec Function

$f(x)= sec^{–1} x$
Let $y = sec^{–1} x$
sec y =x
Differentiating both sides w.r.t. x, we get
$sec y tan y \frac {dy}{dx}=1$
or
$\frac {dy}{dx} =\frac {1}{sec y tan y}$
Clearly we can see that x cannot be -1 or 1 as then it will then become undefined. Therefore $x \in R -[-1,1]$
Also
$tan^2 y=sec^2 y -1$
$tan^2 y =x^2 -1$
As $sec^{–1} x$ lies between $(0, \pi)$, tan y will be positive and negative respectively
Hence
$tan y =\pm \sqrt {x^2 -1}$
Therefore
$\frac {dy}{dx} = \frac {1}{\pm x \sqrt {x^2 -1}} =\frac {1}{ |x| \sqrt {x^2 -1}}$
Domain of f' is R -[-1,1]

## Solved examples

Question 1
Find the derivative of $y = cos^{-1}(3x)$.
Solution
First, recall the derivative of $\arccos(x)$, which is $-\frac{1}{\sqrt{1 - x^2}}$.
Then, apply the chain rule:
$\frac{dy}{dx} = -\frac{1}{\sqrt{1 - (3x)^2}} \cdot \frac{d}{dx}(3x)$ $= -\frac{1}{\sqrt{1 - 9x^2}} \cdot 3$ $= -\frac{3}{\sqrt{1 - 9x^2}}$
Question 2
Find the derivative of $y = x \cdot \arctan(x)$.
Solution
Here, we need to use the product rule, which is $(uv)' = u'v + uv'$, where $u = x$ and $v = tan^{-1}(x)$.
Now The derivative of $\tan^{-1}(x)$ is $\frac{1}{1 + x^2}$.
So,
$\frac{dy}{dx} = 1 \cdot \arctan(x) + x \cdot \frac{1}{1 + x^2}$ $= \arctan(x) + \frac{x}{1 + x^2}$
Question 3
Find the derivative of $y = \frac{\sin^{-1}(x)}{x}$ for $x \neq 0$.
Solution
Apply the quotient rule, $\left( \frac{u}{v} \right)' = \frac{u'v - uv'}{v^2}$, where $u = \sin^{-1}(x)$ and $v = x$.
Now The derivative of $\sin^{-1}(x)$ is $\frac{1}{\sqrt{1 - x^2}}$.
So,
$\frac{dy}{dx} = \frac{\frac{1}{\sqrt{1 - x^2}} \cdot x - \sin^{-1}(x) \cdot 1}{x^2}$ $= \frac{x}{x^2\sqrt{1 - x^2}} - \frac{\sin^{-1}(x)}{x^2}$ $= \frac{1}{x\sqrt{1 - x^2}} - \frac{\sin^{-1}(x)}{x^2}$

Go back to Class 12 Main Page using below links